Virtual Reality Involvement within Project-based Learning towards Student's Speaking Proficiency - Fakhrurriana, Ria; Ningsih, Wety Asri (ELITE Association Indonesia, 2023)
ABSTRACT Popular technology that imitate real life environment called virtual world or virtual reality enables the users to interact with people around the world in many simulated places. Zepeto is one of popular virtual reality games. This research intends to describe the implementation of Zepeto in Intensive Course class, the impact on student's speaking skill, and the student's perception towards the use of Zepeto. Case study was used as research design. The data were gained through observation, questionnaire, rubric, and interview. The participants of this study were 15 students of IC class, first semester students of English Department in IAIN Kediri. The result of this research shows that Zepeto was well-implemented in IC class. Furthermore, the use of Zepeto gives positive impact on student's speaking proficiency. Additionally, the use of Zepeto gained positive response from students. By finishing this study, EFL teachers are suggested to try implementing virtual world game to facilitate students in mastering English speaking. Keywords: Virtual World, Virtual Reality, Speaking, Project-based Learning